SCHOOL MANAGEMENT: CHALLENGES IN THE MEDIATION OF RELATIONSHIPS OF COEXISTENCE - Machado, Cristiane; Martins, Angela Maria (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
This work integrates larger research that analyzes the School Protection System (SPE), a government program implemented in 2010 by the State Department of Education of São Paulo. The objective is to understand, based on data obtained in an exploratory study, carried out in collaboration with Regional Teaching Offices, the opinion of 37 school directors on human and professional relations in school daily life; Relationship of the management with the support network and possible implications of School and Community Mediator Teachers (PMECs) in the school dynamics. A relative contradiction was identified in the directors responses, although the acknowledgment of most of the importance of the PMEC's role in the reduction and mediation of conflict situations in school is perceptible.